Pulmonary lesions consistent with disseminated adiaspiromycosis in egyptian mongooses (Herpestes ichneumon) from Portugal. - Matos, Ana Cristina (2012)
Pulmonary lesions consistent with disseminated adiaspiromycosis in egyptian mongooses (Herpestes ichneumon) from Portugal.